Assessment of the characteristics of carpooling in Metro Manila - Costuna, Clarizza Yvonne C.; Dela Cruz, Ruthie C.
Due to a 24.6% increase in car sales last 2016, more vehicles travel on the road, leading to traffic congestion. One possible way to reduce the volume of cars is through carpooling, which is a nonprofit-driven travel mode among a group of car owners, heading to the same destination on a regular basis. This study aimed to assess the characteristics of carpooling in Metro Manila. An interview and an online survey were conducted to collect data from carpoolers and non-carpoolers. The survey turnout is 206 respondents, 77 of which are Wunder Carpool App users. The Likert Scale was used in analyzing the rating of experiences of both the driver and the passenger. Results have shown that majority of the carpoolers travel to and from highly developed business districts. Potential carpoolers are female employees within the age group of 22 to 40 years old. It was also found out that the current carpooling situation in Metro Manila is not really reducing the traffic congestion because the previous mode of transportation of the carpoolers are public mass transports. Hence, the passengers just transferred modes but the number of cars on the road stays the same. Convenience and comfort are the main reason of engagement by passengers while the fuel cost saving is for the driver. According to five non-carpoolers, safety is the primary reason why they would not dare try carpooling unlike ridesourcing, which considers safety as one of its top reasons in choosing it. Since this was deduced from only five respondents, it is highly recommended to collect more data, especially from non-carpoolers to obtain a more accurate carpooling perspective.